2012
DOI: 10.1002/wow3.3
|View full text |Cite
|
Sign up to set email alerts
|

Employment, job quality and social implications of the global crisis

Abstract: Sluggish recovery of employment after the crisis and worsening job quality. Poverty and inequality on the rise in advanced economies. The sluggish recovery of employment from the crisis is worsened by continuing economic slowdown. Progress in reducing poverty was hampered in many developing countries and the upwards trend in poverty was clear‐cut in the developed world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Women and young workers are likely to be particularly hard hit by this trend (International Labour Office, 2012b). It is estimated that 50 million jobs are missing globally relative to the pre-crisis situation (Curci et al 2012).…”
Section: Changing Labour Force Participation Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Women and young workers are likely to be particularly hard hit by this trend (International Labour Office, 2012b). It is estimated that 50 million jobs are missing globally relative to the pre-crisis situation (Curci et al 2012).…”
Section: Changing Labour Force Participation Ratesmentioning
confidence: 99%
“…In these ways, unemployment has an impact on overall employment quality and the presence of informal work arrangements, within which workers typically lack adequate social protection and coverage by social dialogue arrangements. A study by Curci et al (2012) shows that diverging employment trends and slow recovery from the crisis increase the risk of social unrest. The authors report that in 57 out of 106 countries the economic situation worsened between 2010 and 2011.…”
Section: Long-term Unemployment On the Rise Leading To Inequality And...mentioning
confidence: 99%
“…The incidence of temporary employment has increased during the past few decades in the U.S. and the majority of other OECD countries (Autor, 2003;Curci, Rani, and Sekerler Richiardi, 2012;OECD, 2014). Since temporary workers generally have lower job security and poorer working conditions than regular workers, the increase in temporary employment is considered problematic as it may lead to an increase in labor market segregation among workers.…”
Section: Introductionmentioning
confidence: 99%
“…They have shown that individuals with lower income, less education, and precarious housing conditions have been more vulnerable to the negative impacts of COVID-19, experiencing higher rates of infection and mortality (Blundell et al 2020). Additionally, following Curci et al (2012) results, they also showed that occupation played a significant role, with essential workers facing increased exposure to the virus, while those in higher-status professions were often more resilient due to the ability to work remotely and access better healthcare resources (Collins et al 2020).…”
mentioning
confidence: 97%